Electroconductive 3D polymeric network production by using polyaniline/chitosan-based hydrogel - ALEMDAR YAYLA, NESLİHAN (ELSEVIER SCI LTD, 2018)
Herein, polyaniline/chitosan(PANI/CTS)-based electroconductive hydrogel was produced by photocrosslinked network in which CTS was used as a main component. Firstly, glycidyl methacrylate (GMA) was grafted on the CTS backbone to form CTS-g-GMA. Then, a three-dimensional polymeric network consisting of CTS-g-GMA and poly(ethylene glycol) diacrylate (PEGDA) was obtained by using photocrosslinking technique. At last, aniline monomer solution prepared by utilizing three different aniline concentrations (0.08, 0.16 and 0,32 M) was absorbed into (CTS-g-GMA)-PEGDA crosslinked structure to form [(CTS-g-GMA)-PEGDA]-PANI electroconductive semi interpenetrating network. FT-IR, XRD, SEM, TGA analyses and cytotoxicity test were performed for the produced samples. Conductivities of the hydrogels were determined by four-point probe technique. According to the conductivity measurements, among the PANI/CTS-based hydrogels, [(CTS-g-GMA)-PEGDA]-PANI(0.32 M) has the highest conductivity value (7437x10(-3)S/cm). The obtained results showed that the fabricated electroconductive hydrogel (ECHs) in this study is a promising candidate owing to its advantages for biomedical applications especially biosensors in the future.
Keywords: Chitosan; Polyaniline; Photocrosslinking; Electroconductive hydrogel; ELECTRICALLY CONDUCTIVE HYDROGELS; CHITOSAN-GRAFTED POLYANILINE; INJECTABLE HYDROGELS; FUEL-CELLS; ACID; ANTIBACTERIAL; MEMBRANES; SALT; COMPOSITES; CHEMISTRY